Structure, binding energies, and IR-spectral fingerprinting of formic acid dimers - YAVUZ, İLHAN (AMER CHEMICAL SOC, 2008)
We describe equilibrium structures for a variety of species likely to be formed as intermediate species in the dimerization of formic acid to produce the stable C-2h-symmetric doubly H-bonded dimer and perhaps produced as the vapor is irradiated. For several low-lying species the rearrangement pathways to the stable form are characterized at the MP2/6-311+G-(d,p) level of theory, with optimized structures and vibrations computed with full counterpoise corrections for basis set superposition error. Estimates of vibrational frequencies with corrections for anharmonicity suggest that infrared transitions (CO stretches and OH out-of-plane motions) could signal the presence of species less stable than the C-2h dimer, observable in irradiation studies of formic acid vapor.
Keywords: WATER DIMER; CARBOXYLIC-ACIDS; GAS-PHASE; BASIS-SET; SPECTROSCOPY; VIBRATIONS; DYNAMICS; SURFACES